Stratigraphy and structural style of Souk Ahras foreland fold-thrust belt in northeastern Algeria - Abdallah CHABBI; Asma CHARMITI; Stéphane BRUSSET (My University, 2021)
In northeastern Algeria, the Souk Ahras foreland basin is a part of the Maghrebides fold-thrust belt and comprises Sellaoua and Medjerda High units in the footwall of Tellian thrust sheets. Detailed geological mapping supported by micro-paleontological, petrographic, and structural data allows us to reappraise its stratigraphy and its structural style and to characterize the relationship between the different structural units (Numidian, Tellian, Sellaoua, and Medjerda High units). Data were collected for a biostratigraphy and field observations along to six (06) sections spread over the Ouled Driss, Dj. Boubakhouch, Dj. Boukebch – Dekma, and the Medjerda High. The Souk Ahras foreland basin substrate is made up by Jurassic and early Cretaceous series and constituted an outer shelf pre-foreland passive margin where salt tectonics occurred. From upper Cretaceous to Miocene, flexural subsidence and thrust wedge propagation took place as the result of the northward drift of Africa plate. The Souk Ahras foreland is finally deformed by thrust-related folds, which affected a pre shortening tectonic pile involving remnant of salt tectonics influenced margin during at least Cretaceous times